Achievements and prospects of applying high-throughput sequencing techniques to potato genetics and breeding - I. V. Bykova; N. A. Shmakov; D. A. Afonnikov; A. V. Kochetov; E. K. Khlestkina (Вавиловский журнал генетики и селекции, 2017)
In recent years, marker-assisted selection (MAS) has been intensively used to increase potato breeding efficiency. Large-scale studies of the potato genome and genes exploiting next-generation sequence (NGS) approaches are required for broad application of MAS, genomic selection as well as genomic editing (the newest approach for creating potato with desired properties). In this review, trends in potato NGS-based research are overviewed, and related Internet resources are systematized. Special attention is given to peculiarities of the models and the approaches used in potato genetic studies, taking into account the complex organization of its genome and a high level of heterozygosity. In genetic studies diploids are used often, including diploid potato species, artificially obtained heterozygous dihaploids and homozygous double monoploids. The availability of artificially created diploid forms played an essential role in potato genome sequencing, which was completed in 2011. The Potato Genome Sequencing Consortium activities included not only constructing genome libraries, sequencing, assembling and annotation of the genome, but also genome sequence-based investigations uncovering features of potato genome evolution, SNP identification, analysis of genes and gene networks regulating resistance to phytopathogens and technological characteristics. An important outcome of the genome sequencing was further identification of more than 8 thousand SNPs and approbation of the Genotyping-by-sequencing (GBS) method on potato, which is the basis for potato genomic selection and for discovery of economically important genes using genome wide association studies (GWAS). Optimization of existing bioinformatic tools to support these studies, taking into account potato genome organization peculiarities, are carried out. This review gives analysis of databases containing potato genome and transcriptome sequencing results, as well as accompanying resources. This information should prove useful while planning comparative assays of potato transcriptome or application of DNA-markers. Sequencing of the genome as well as transcriptomes and microRNomes of cultivated potato and its wild relatives, on one hand, is of fundamental interest, assisting in detecting features of genome evolution, ontogenetic development and mechanisms of various environmental stresses responses. On the other hand, it is the basis for a wide range of practical applications for developing effective genomic and gene-specific markers and marker-assisted breeding of new potato cultivars with desired properties.